Evaluation of CABS score based on vitals in children at admission for prediction of severity of illness and outcome - Mekala, Aparajitha; Chandrasegaran, Barathy; Babji, N. Shivaramakrishna; Kumar, Vellamki Brahma (International Journal of Contemporary Pediatrics, 2021)
Background: Triage in an emergency is sorting out the patients based on the severity of illness and prioritizing care accordingly. Kumar et al devised a score taking temperature, heart rate, respiratory rate, blood pressure, capillary refill time, oxygen saturation, and sensorium. We propose to evaluate a sickness scoring system based on capillary refill time, sensorium using AVPU score, blood pressure, and oxygen saturation by pulse oximetry (CABS) which are least affected by stress, anxiety, temperature, acidosis, etc. Methods: Prospective study in children admitted consecutively in the age group one month to 12 years from 1st January 2019 to 31st December 2019, to paediatric intensive care unit. Triage score applied at the time of the first contact. Each variable in the study was scored as 0 for being normal and a score of 1 for being abnormal. The total score for each child is obtained. The outcome at discharge was correlated with the study variables and total score. ROC curve analysis was done for the overall predictive ability of the score. Results: Of 346 children admitted, 27 expired, and 319 children were discharged. The risk of mortality increased with the increasing score. CFT, sensorium, blood pressure, and oxygen saturation are all significantly associated with mortality. A cut-off score of 2 has the highest sensitivity and specificity of 96.3% and 70.2%. The total score has 90% predictive accuracy as AUC is 0.913. Conclusions: As no special training is required for its implementation, the score is promising as a triage tool in resource-poor settings.